Compensation of Polarization Mode Dispersion - Gupta, Ritu (My University, 2007)
The topic of thesis is “Compensation of Polarization Mode Dispersion (PMD)” in Fiber optics communication and its impact on high speed data transmission. The work can be divided into three parts which deals with major aspects of PMD: characteristics, transmission and compensation. Polarization-mode dispersion (PMD), in single-mode optical fibers, is a phenomenon that a limit the bit-rate-distance product of amplified, lightwave communication systems. However, compensation is complicated due to the random nature of PMD. Therefore, adaptive compensation techniques are required. We modified the PMD compensation system that was earlier developed and made it robust and bit-rate independent. The impact of PMD in transmission systems has also been investigated. The effect of using solitons has also been quantified in both conventional and dispersion managed, PMD distorted systems and. The new set-up uses the degree of polarization (DOP) of the received optical signal for monitoring the fiber-link's PMD. By simulation we analyze the affec of PMD on the fiber optic system. At high bit rate PMD has a great effect on the system. As the bit rate increases the dispersion due to two modes. This is due to polarization. The intent of which is that of making the performance of a coherent optical receiver insensitive to the polarization transformations occurring along the optical fiber, without resorting to polarization compensation or control. The principle on which polarization spreading operates is that of spreading the signal power over different states of polarization, some classes of spreading waveforms satisfying the above condition, the derivation of the structure and performance of optimum receivers in Gaussian noise. In this thesis we discuss the compensation techniques of PMD and make their simulation set-ups to compensation the orders of the PMD according to those set-ups.
Keywords: Polarization Mode Dispersion; Degree of Polarization; PMD; PSP Method; Modeling for Compensation of PMD; Optical Fibre